NILAI MORAL DALAM DONGENG KEPINGAN EMAS DARI LANGIT PADA KANAL YOUTUBE RIRI CERITA ANAK INTERAKTIF - Dhini Akhiriani (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to identify the themes and moral values contained in the fairy tale Kepingan Emas dari Langit uploaded on the YouTube account Riri Cerita Anak Interaktif. The research method used is descriptive qualitative with the method of reading and recording. Data collection from 6 in-dicators of moral values found in the story, the results of the analysis show that this fairy tale teaches values such as sincerity, fortitude, independence, gratitude, filial piety to parents and not greedy. The moral values contained therein are important for children's character building and can serve as an effective educational tool.